Pengungkapan Corporate Social Responsibility Terhadap Agresivitas Pajak - Darti Djuharni; Wahyu Alif Kurniawan (JIATAX (Journal of Islamic Accounting and Tax), 2020)
The purpose of this study aims to analyze the disclosure of Corporate Social Responsibility (CSR) on corporate tax aggressiveness. The independent variable of this study is corporate social responsibility (CSR) using the dummy method and based on the standard GRI G-4 / GRI index and the dependent variable of this study is the tax aggressiveness required with an effective tax rate proxy (ETR). This study uses control variables including profitability, leverage, capital intensity, and inventory intensity. The study uses secondary data conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 and the study sample was obtained by 11 companies. The research method used uses multiple linear regression with the help of SPSS 22 software. The results of this study prove that the disclosure of Corporate Social Responsibility is not significant for tax aggressiveness